2012
DOI: 10.1016/j.jcat.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry of phase-pure M1 MoVTeNb oxide during operation in selective oxidation of propane to acrylic acid

Abstract: The surface of a highly crystalline MoVTeNb oxide catalyst for selective oxidation of propane to acrylic acid composed of the M1 phase has been studied by infrared spectroscopy, microcalorimetry, and in-situ photoelectron spectroscopy. The acid-base properties of the catalyst have been probed by NH3 adsorption showing mainly Brønsted acidity that is weak with respect to concentration and strength of sites. Adsorption of propane on the activated catalyst reveals the presence of a high number of energetically ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
188
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(207 citation statements)
references
References 59 publications
11
188
0
8
Order By: Relevance
“…13,[23][24][25][26][27][28][29][30][31][32][33] In this sense, López-Nieto et al have reported an important tellurium loss during thermal treatment activation of catalyst, which is commonly performed at 600 °C under nitrogen. 34 Indeed, the Mo/Te ratio increases when increasing the niobium oxalate content, since, oxalate anions act as reducing agent, which enhances the reduction degree of tellurium cations, rendering it instable and easily removal from the crystalline structures.…”
Section: -24mentioning
confidence: 99%
“…13,[23][24][25][26][27][28][29][30][31][32][33] In this sense, López-Nieto et al have reported an important tellurium loss during thermal treatment activation of catalyst, which is commonly performed at 600 °C under nitrogen. 34 Indeed, the Mo/Te ratio increases when increasing the niobium oxalate content, since, oxalate anions act as reducing agent, which enhances the reduction degree of tellurium cations, rendering it instable and easily removal from the crystalline structures.…”
Section: -24mentioning
confidence: 99%
“…It was observed [26] that the surface composition of the M1 phase differs significantly from the bulk, implying that the catalytically active sites are not part of the M1 crystal structure and rather part of all terminating planes. It then appeared that the active sites are formed under propane oxidation conditions and are embedded in a thin layer enriched in V, Te, and Nb on the surface of the stable self-supporting M1 phase [23]. This example shows how complex a catalytic surface can be and how the surface structure and chemical composition may change under reaction (working) conditions.…”
Section: Introduction To Metal Oxide Catalystsmentioning
confidence: 98%
“…In a study using microcalorimetry, Schlögl et al have shown [23] that, on an activated mixed oxide MoVTeNb-O catalyst, active for propene and propane selective oxidation and ammoxidation to acrylic acid and acrylonitrile, respectively, the adsorption energy of propene and propane are about constant vs. coverage (57 kJ·mol −1 ). However, after reaction the energy decreases and its distribution in strength becomes heterogeneous, as illustrated in Figure 4.…”
Section: Introduction To Metal Oxide Catalystsmentioning
confidence: 99%
“…The mobility of Te in the presence of water vapor (steam) causes the enhanced selectivity to acrylic acid [17,75]. Adsorption of propane after catalysis shows a decrease of the heat of adsorption, which implies that the surface is restructured during the reaction [17]. This surface restructuring also indicates that active sites do not contain all the elements of the M1 phase and the surface composition of the M1 phase differs greatly from the bulk.…”
Section: Selective Oxidation Of Propane To Acrylic Acidmentioning
confidence: 99%